TANGGUNG JAWAB PERUSAHAAN MULTINASIONAL DALAM KEBAKARAN HUTAN DI INDONESIA - Chris Sostom Gintoe (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The economies of countries, especially developing countries, are in need of a steady flow of foreign capital to support an economy that can continue and grow. One of the choices for economic growth to run the economy is to invite multinational companies to invest or carry out economic activities that can support the lives of people in developing countries. The presence of multinational companies in the economies of countries is often facilitated by providing facilities and facilities for foreign investment in their countries. Multinational companies are one of the most talked about forms of business associations in the context of world and economic globalization. The role of globalization as an ideology and the development of regulatory policies related to multinational companies. Forest fires that occur in Indonesia can be called a serious violation of international environmental law. Air pollution due to forest pollution is very contrary to the principles of international environmental law. Among the principles of Sic Utere Tuo ut alienum non laedes which confirms that a country is prohibited from carrying out or allowing activities that can harm other countries, as well as the principle of good neighborliness said that the sovereignty of a country's territory should not be disturbed by other countries. Keyword: Responsibility, Multinational Corporations, Forest Fires, Environmental Law, International Law.